2018
DOI: 10.1103/physrevb.98.195447
|View full text |Cite
|
Sign up to set email alerts
|

Possible flexoelectric origin of the Lifshitz transition in LaAlO3/SrTiO3 interfaces

Abstract: Multiple experiments have observed a sharp transition in the band structure of LaAlO3/SrTiO3 (001) interfaces as a function of applied gate voltage. This Lifshitz transition, between a single occupied band at low electron density and multiple occupied bands at high density, is remarkable for its abruptness. In this work, we propose a mechanism by which such a transition might happen. We show via numerical modeling that the simultaneous coupling of the dielectric polarization to the interfacial strain ("electro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 64 publications
(96 reference statements)
2
11
0
Order By: Relevance
“…Close to the crossing region, stronger mixing between the d xy -like and d yz/zx -like bands will neutralize the orbital polarization. This trend is consistent with previous computational works [46,47], where it has been shown that the d xy orbital filling is less at higher energy region. At the same time, the relative contribution of the different orbitals can be controlled by tuning the heterostructure's parameters such as STO thickness.…”
Section: Orbital Polarizationsupporting
confidence: 93%
“…Close to the crossing region, stronger mixing between the d xy -like and d yz/zx -like bands will neutralize the orbital polarization. This trend is consistent with previous computational works [46,47], where it has been shown that the d xy orbital filling is less at higher energy region. At the same time, the relative contribution of the different orbitals can be controlled by tuning the heterostructure's parameters such as STO thickness.…”
Section: Orbital Polarizationsupporting
confidence: 93%
“…Indeed, interface states are absent for all J 1 values up to 400 meV. While this lack of interface states is consistent with previous calculations [41], it is not consistent with experiments [56,57], and likely points to some additional missing physics in the model [41].…”
Section: Resultssupporting
confidence: 49%
“…The latter increases the physical layer thickness of the dielectric effectively by 0.8 nm to about 2.3 nm. The physical distance between the gate charge and the 2DEG is probably even larger as the charges presumably reside deep inside the SrTiO 3 substrate [8]. We argue this to be the origin of the low gate leakage current in our devices.…”
Section: Device Structurementioning
confidence: 80%